The Functional Competence of the Geographic Distribution for the Educational Services in al-Qa’im City by Using the Geographical Information Systems - Ali, Ahmad Mahmoud (Al-Adab Journal, 2019)
The research steps have focused on the study of the reality of the educational services in al-Qa’im City via recognizing the number of the pupils, students, the number of the classrooms, the number of the staffs in the two grades (intermediate and the secondary ) and compare them with the local planned criteria, used by the Iraqi ministry of planning, in order to find out the range of competence of this service and its suitability to the people of the city . It is found out that the study community includes about (56 %) of the total number of the intermediate pupils in the district in general. It is about ( 65%) of the total number of the secondary and the preparatory grades students along the district. It Is opposed by a clear deficiency in the numbers of the staffs that reached (28%) and (33%) from the total number of the intermediate and secondary teaching staffs along the district. Besides the research focuses on the geographical distribution competence for the educational establishments via using the two approaches of the neighboring connection relation and the standard distance to recognize the distribution type and the range of its affect inside the residential alleys ( the study community).